Maintenance Integration in Equipment Design Process for Africa - Azouma, Ouézou Yaovi; Giroux, François (Bangladesh Journal of Scientific and Industrial Research, 2010)
The integration of the maintenance as soon as possible in the design allows reducing the possession cost of equipment. This factor being major for the users of agricultural and food processing equipments in Africa, the objective of this study was to answer this requirement. In order to satisfy this need, a critical approach of the tools developed in the industrialized countries and an analysis of the maintenance practices in developing countries permit to suggest several tools and recommendations for integration of the maintenance in the design. Key words: Africa, Design, Equipment, Integrated maintenance DOI: 10.3329/bjsir.v44i3.4405 Bangladesh J. Sci. Ind. Res. 44(3), 319-326, 2009